Community Empowerment in Knowing Sources of Natural Antioxidants Through Hydroponic Systems - Nurmeily Rachmawati; Syarah Anliza (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
Health is one of the main pillars of human life. The quality of health of a country or a person can be affected by the development of the disease. Based on the results of the Basic Health Research (Riskesdas) in 2018, degenerative diseases showed an escalation. These diseases originate from environmental factors that have decreased in quality. One of them is the emergence of free radical compounds. These free radicals can oxidize nucleic acids and initiate degenerative diseases. Antioxidants are able to ward off free radicals which can be obtained from natural sources. One of the natural sources of these antioxidants is plants. The method used in this service activity is community education through counseling activities and hydroponic system skills training that can be applied at residents' homes using simple tools and materials. The purpose of this service activity is to increase public knowledge about sources of natural antioxidants and training on hydroponic systems. The implementation of this service activity was carried out in RW013 Gebang Raya Village, Periuk District, Tangerang. The results of the service showed an increase number in knowledge which was originally 42% to 66% from the results of the pretest and posttest that has been carried out. The knowledge indicators provided information including the definition of antioxidants, knowledge of free radicals, sources of antioxidants, and last but not least natural and artificial antioxidants. The residents also gained skills improvement from learning through a hydroponic system using kale, spinach, pokcoy, and lettuce as sources of natural antioxidants.